2012
DOI: 10.4161/onci.19407
|View full text |Cite
|
Sign up to set email alerts
|

Interleukin 21 impairs tumor immunosurveillance of colitis-associated colorectal cancer

Abstract: The pathogenesis of colitis-associated colorectal cancer is strongly influenced by immune cells, cytokines and other immune mediators present in the inflamed colon. Current research has emerged that T helper cell associated cytokines play a prominent role in tumor growth. In our recent manuscript we have revealed that the Th17 associated cytokine IL-21 prominently influences tumor development and immunosurveillance of colitis-associated colorectal cancer.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
14
1

Year Published

2012
2012
2022
2022

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 14 publications
(16 citation statements)
references
References 8 publications
1
14
1
Order By: Relevance
“…Although both IL-17A and IL-17F are required for spontaneous CRC tumorigenesis [123, 125], in chemically induced colitis and in CAC tumorigenesis they play quite opposing roles [122, 126][124]. IL-17A deficient mice develop less CAC tumors of smaller size, underscoring the role of IL-17A in regulation of intestinal inflammation [127, 128], intratumoral inflammation [129, 130],, and tumor growth [122, 126, 130]. APC Min mice with established B. fragilis infection and chronic colitis exhibit lower tumor burden when IL-17A is neutralized [77].…”
Section: Inflammation As a Stimulator Of Cac Growth- Role Of Inflammamentioning
confidence: 99%
“…Although both IL-17A and IL-17F are required for spontaneous CRC tumorigenesis [123, 125], in chemically induced colitis and in CAC tumorigenesis they play quite opposing roles [122, 126][124]. IL-17A deficient mice develop less CAC tumors of smaller size, underscoring the role of IL-17A in regulation of intestinal inflammation [127, 128], intratumoral inflammation [129, 130],, and tumor growth [122, 126, 130]. APC Min mice with established B. fragilis infection and chronic colitis exhibit lower tumor burden when IL-17A is neutralized [77].…”
Section: Inflammation As a Stimulator Of Cac Growth- Role Of Inflammamentioning
confidence: 99%
“…As a promising cytokine for cancer immunotherapy, whilst IL-21 suppresses growth in certain tumors, including renal cell carcinoma and melanoma (9,14), it may promote growth in others, including colitis-associated colorectal cancer and follicular lymphoma (11,15). The function of IL-21 is complex, as it appears to have different functions in different tumors.…”
Section: Discussionmentioning
confidence: 99%
“…Studies have suggested that IL-21 is capable of suppressing growth in certain tumors, and it has already been used in phase I or II trials of patients with melanoma and renal cell carcinoma, with promising antitumor results obtained (9,10). However, IL-21 may also promote growth in certain other tumors, including colitis-associated colorectal cancer by impairing tumor immunosurveillance (11). Therefore, the function of IL-21 is extremely complex, as its use in different cancers has been shown to lead to different results (911).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…IL-21 was produced in excess in the gut of patients with UC-associated colon cancer [82]. This cytokine has a prominent function in tumor growth and immunosurveillance of colitis-associated tumorigenesis [83]. In mice with colitis-associated colon cancer (CAC) induced by azoxymethane (AOM) and dextran sulfate sodium (DSS), IL-21 was highly expressed in the intestines.…”
Section: Il-21 In Disorders Of Gastrointestinal Systemmentioning
confidence: 99%